The Effect of Counseling Intervention on Adolescents' Knowledge Regarding Sunscreen Use and the Incidence of Acne Vulgaris: An Experimental Study in the Adolescent Population in Jakarta, Indonesia - Shelma Tria Amanda; Tansil Tan, Sukmawati (Community Medicine and Education Journal, 2024)
Acne vulgaris is a common skin problem in adolescents, often exacerbated by a lack of knowledge about proper skin care, including the use of sunscreen. This study aims to evaluate the effectiveness of counseling interventions in increasing adolescents' knowledge about sunscreen use and reducing the incidence of acne vulgaris. This experimental research involved 150 adolescents aged 15-18 years in Jakarta who were randomly divided into an intervention group (receiving counseling) and a control group. The intervention group received structured counseling sessions on sunscreen use and skin care for 8 weeks. Knowledge about sunscreen and the incidence of acne vulgaris were assessed before and after the intervention using a validated questionnaire and clinical examination. There was a significant increase in knowledge about sunscreen in the intervention group after counseling (p < 0.001). The intervention group also showed a significant reduction in the incidence of acne vulgaris compared to the control group (p = 0.023). Counseling interventions are effective in increasing adolescents' knowledge about sunscreen use and reducing the incidence of acne vulgaris. This intervention can be considered as a public health strategy to address skin problems in adolescents.